Pendugaan erosi menggunakan metode Modified Universal Soil Loss Equation (MUSLE) di Sub DAS Bale - Salviya, Lujeng Luthvy; Taryana, Didik; Masruroh, Heni; Aristin, Nevy Farista (Universitas Negeri Malang, 2023)
The Bale River Sub Basin is located in Tulungrejo Village, Gandusari District, Blitar Regency, on territory with undulating topography and at an elevation of 519 to 846 meters above sea level, with steep to extremely steep slopes. The majority of the Bale sub-watershed area's land use, notably forests, has been transformed into agricultural land or mixed gardens, where land conversion is carried out without or with conservation measures under adverse land cover conditions. Land use that does not comply with land conservation requirements exposes the Bale sub-watershed to erosion, and the Bale sub-watershed has steep slopes. As a result, this research aims to forecast the quantity of erosion in the Bale sub-watershed. This study employed a literature review and a field survey, with data collected in the form of primary and secondary sources. The MUSLE (Modified Universal Soil Loss Equation) approach was used for data analysis to estimate the amount of erosion in the research area. According to the findings of this study, the Bale sub-watershed has 18 land units, with land unit 4 having the highest erosion value of 647,99 tons per hectare per year. Land unit 4 has a Vq factor value of 2.322,76 m3, a K value of 0.50, an LS value of 1.7, and a CP value of 0.60 with residential land use and no conservation activities. Meanwhile, land unit 17 had the lowest erosion value of 1,09 tons per hectare per year. The Vq value for the land unit is 686,05 m3, the K value is 0.30, the LS value is 3.8, and the CP value is 0.02 using forest land and conservation methods such as bunds and reinforcing grass. Sub Daerah Aliran Sungai Bale berada di Desa Tulungrejo, Kecamatan Gandusari, Kabupaten Blitar yang memiliki lahan dengan topografi yang bergelombang dan berada pada ketinggian antara 519 – 846 mdpl dan didominasi dengan kelerengan yang curam hingga sangat curam. Penggunaan lahan di sebagian besar wilayah sub DAS Bale, yaitu berupa hutan telah banyak berubah menjadi lahan pertanian atau kebun campuran. Dimana alih fungsi lahan tersebut dilakukan tanpa atau dengan tindakan konservasi dan kondisi penutup lahan yang kurang baik. Pemanfaatan lahan yang tidak sesuai dengan ketentuan konservasi lahan akan berakibat pada kerentanan sub DAS Bale terhadap kejadian erosi, ditambah Sub DAS Bale memiliki kemiringan lereng yang curam. Dengan demikian, tujuan dari kajian ini adalah untuk menduga/prediksi besaran erosi di Sub DAS Bale. Metode yang digunakan dalam penelitian ini adalah studi literatur dan survei lapangan dengan data yang digunakan berupa data primer dan sekunder. Analisis data dilakukan dengan menggunakan metode MUSLE (Modified Universal Soil Loss Equation) untuk pendugaan besarnya erosi pada wilayah kajian. Hasil dari penelitian ini, terdapat 18 unit lahan di Sub DAS Bale dengan nilai erosi terbesar pada unit lahan 4 sebesar 647,99 ton/ha/tahun. Satuan unit lahan 4, memiliki nilai faktor Vq sebesar 2.322,76 m3, nilai K sebesar 0,50, nilai LS sebesar 1,7 dan nilai CP sebesar 0,60 dengan penggunaan lahan permukiman tanpa adanya upaya konservasi. Sementara itu, nilai erosi terkecil terdapat pada unit lahan 17 sebesar 1,09 ton/ha/tahun. Nilai Vq pada unit lahan tersebut sebesar 686,05 m3, nilai K sebesar 0,30, nilai LS sebesar 3,8, dan nilai CP sebesar 0,02 dengan penggunaan lahan hutan serta upaya konservasi berupa guludan dan rumput penguat.